2001
DOI: 10.1046/j.0022-0477.2001.00574.x
|View full text |Cite
|
Sign up to set email alerts
|

Shading by shrubs in a desert system reduces the physiological and demographic performance of an associated herbaceous perennial

Abstract: Summary1 A 2-year field study examined the demographic consequences of association with shrubs in an herbaceous perennial, Cryptantha flava . Physiological data were collected to evaluate whether shrub effects were mediated primarily through water, nutrient or light availability. 2 Microclimatic conditions under the north side of shrubs differed from open microhabitats, primarily in light availability. Due to little photosynthetic acclimation to light, daily photosynthesis for plants under shrubs was reduced p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
64
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 51 publications
9
64
0
Order By: Relevance
“…However, some authors either reported no change (Hubick 1990) or a decrease of d 13 C (more negative values) in response to N fertilisation (Bender and Berge 1979;Guehl et al 1995). In the case of PAR availability, several studies have reported a decrease of d 13 C (more negative) when PAR was reduced (Vora et al 1989; Relationships between leaf carbon dioxide assimilation rate (lmol m À2 s À1 ), leaf conductance (mmol m À2 s À1 ), leaf intrinsic water use efficiency (mmol mol À1 ) and soil volumetric water content at 0-20 cm (%) in Pinus sylvestris seedlings grown without vegetation (P) and with vegetation (P+veg), and for one of the most abundant grass species of the plot (Dactylis glomerata Forseth et al 2001;Staples et al 2001). However, as pointed out by Farquhar et al (1989), interpreting the influences of light on d 13 C under field conditions is confounded by the fact that plants, especially those in the shaded understory, may recycle respired CO 2 that has a different d 13 C signature than that of the atmosphere (À8&).…”
Section: Discussionmentioning
confidence: 98%
“…However, some authors either reported no change (Hubick 1990) or a decrease of d 13 C (more negative values) in response to N fertilisation (Bender and Berge 1979;Guehl et al 1995). In the case of PAR availability, several studies have reported a decrease of d 13 C (more negative) when PAR was reduced (Vora et al 1989; Relationships between leaf carbon dioxide assimilation rate (lmol m À2 s À1 ), leaf conductance (mmol m À2 s À1 ), leaf intrinsic water use efficiency (mmol mol À1 ) and soil volumetric water content at 0-20 cm (%) in Pinus sylvestris seedlings grown without vegetation (P) and with vegetation (P+veg), and for one of the most abundant grass species of the plot (Dactylis glomerata Forseth et al 2001;Staples et al 2001). However, as pointed out by Farquhar et al (1989), interpreting the influences of light on d 13 C under field conditions is confounded by the fact that plants, especially those in the shaded understory, may recycle respired CO 2 that has a different d 13 C signature than that of the atmosphere (À8&).…”
Section: Discussionmentioning
confidence: 98%
“…Lateral root architecture is also likely to be important in the maintenance of C. flava as a persistent sub-dominant species in the nutrient limited environment where it occurs. The much larger shrubs Artemisia tridentata and Chrysothamnus nauseosus dominate the plant biomass in this community and are capable of suppressing growth of C. flava due to asymmetric competition for light (Forseth et al, 2001). However, even in the presence of reduced light, C. flava was able to acquire spatially variable N, which resulted in increased growth and reproduction (Peek and Forseth, 2003a).…”
Section: Discussionmentioning
confidence: 98%
“…Annual precipitation at the nearby Vernal airport weather station averages 208 mm and is highly variable (coefficient of variation of monthly rainfall ranges from 50 to 125% of the mean). The presence of rock outcrops, soil depth differences, shrubs, and variable drainage patterns generate a considerable amount of spatial heterogeneity in water availability and solar radiation (Forseth et al, 2001).…”
Section: Study Species and Systemmentioning
confidence: 99%
“…Comparative analyses of patterns among and within coexisting species can suggest differences between intra-and interspecific interactions (e.g., Fonteyn and Mahall 1981;Haase et al 1996). We also took the directionality of spatial patterns into account, because desert plants on the more shaded northern side of neighbors may be positively or negatively affected by the shade (Forseth et al 2001).…”
Section: Introductionmentioning
confidence: 99%